Synthesis of poly(methyl methacrylate)-b-poly[(4-vinylphenyl)dimethylsilane] via atom transfer radical polymerization and its in-chain functionalization. Issue 4 (13th December 2019) - Chavan, Vijay; Seo, Kwang Su; Wesdemiotis, Chrys; Quirk, Roderic P.
Abstract : Methyl methacrylate was successfully copolymerized with (4-vinylphenyl)dimethylsilane in toluene via ATRP in the presence of a silyl hydride group and the copolymer was subjected to in-chain functionalization by hydrosilation. Abstract : This research paper describes a general method to synthesize functional polymers using a combination of atom transfer radical polymerization and hydrosilation. Methyl methacrylate (MMA) was copolymerized with (4-vinylphenyl)dimethylsilane (VPDS) in toluene via atom transfer radical polymerization (ATRP). The presence of a silyl hydride bond was proven using MALDI-ToF, NMR and IR spectra. The ability of the copolymer to undergo hydrosilation reaction was confirmed by reacting it with allyl alcohol. The expected molecular weight increase of the final polymer after functionalization was in agreement with the observed molecular weight. This method can be used to control both the type and quantity of functionalization by varying the amount of VPDS in the monomer feed.